Navigating Innovation How to Identify, Prioritize and Capture Opportunities for Strategic Success - Gailly, Benoit (Springer International Publishing, 2018)
Every firm must maintain an entrepreneurial ecosystem and a coherent innovation strategy in order to stay ahead of the competition. For managers this means being able to build a vision of what innovation looks like in the context of their organization, fostering entrepreneurial behaviour, spotting opportunities and making the right decisions. Based on years of practical experience and unique insight, this handy guide identifies fundamental challenges and is rooted in concrete examples. Accompanied by a brand new app for iPhone and Android as well as a companion website, this is an easy dip in, dip out guide with a focus on successful execution. Navigating Innovation is a one-stop-shop, giving you a deeper understanding of the core concepts and tools to capture the right opportunities for your business. .